(untitled) (Bodhi Path, 2025)
This paper re‑evaluates women’s roles in ancient India, tracing their trajectory from the relative autonomy of the early Vedic period to the patriarchal constraints codified in later texts like the Manusmriti. Drawing on literary, epigraphic and artistic evidence, it highlights female scholars, ritual partners and royal diplomats; analyses the impact of Buddhist and Jain monastic orders in offering alternative spaces for agency; and reads epic heroines and goddess iconography as cultural barometers of gender ideals. Despite increasing marginalisation, women continually negotiated power within domestic, religious and political spheres. Understanding this complexity enriches broader debates on gender and historiography.